PENGEMASAN TARI RAPA’I GELENG DALAM BENTUK MODUL UNTUK SISWA KELAS XI SEKOLAH MENENGAH ATAS - Hartati Dwi Lestari Marbun; Yusnizar - Heniwaty (Gesture: Jurnal Seni Tari, 2021)
ABSTRACT - The Rapa'i Geleng dance module is the result of research that has been carried out for teaching materials in Class XI Atasa Middle School. In this study using the theory of Cahyorini and Rusfian (2011: 28): "Packaging is an activity consisting of graphic design, product information and design structure". Rudi Susilana and Cepi Riyana (2017: 15): "A module is a program package that is arranged in certain units and is designed in such a way for the learning interests of students". This type of research is qualitative. Data collection techniques are observation, interview and documentation. The data analysis technique was in the form of laboratory work carried out in the Dance Education Study Program at the State University of Medan. The product of this research is in the form of module teaching materials which are packaged with packaging procedures, namely the planning stage, the implementation stage and the evaluation stage. The compiled modules contain the syllabus, lesson plans and learning material for the Rapa'i Geleng dance based on KD 3.1, namely concepts, techniques and procedures. Based on the material and media feasibility test, the score was 4.66 from the material expert validation test, a score of 4.6 from the media expert validation test. This score proves that the Rapa'i Geleng dance learning module is very well used as teaching material by teachers in learning dance for high school class XI students. Keywords: Packaging, Rapa'i Geleng Dance, Module            ABSTRAK - Modul tari Rapa’i Geleng merupakan hasil penelitian yang telah dilakukan untuk bahan ajar di Sekolah Menengah Atasa kelas XI. Dalam penelitian ini menggunakan teori Cahyorini dan Rusfian (2011:28): “Pengemasan adalah kegiatan yang terdiri dari desain grafis, informasi produk serta struktur desain”. Rudi Susilana dan Cepi Riyana (2017:15): “Modul adalah suatu paket program yang disusun dalam bentuk satuan tertentu dan didesain sedemikian rupa guna kepentingan belajar siswa”. Jenis penelitian ini adalah Kualitatif. Teknik pengumpulan data adalah observasi, wawancara dan dokumentasi. Teknik analisis data berupa kerja laboraturium yang dilakukan di Program Studi Pendidikan Tari Universitas Negeri Medan. Produk dari penelitian ini berupa bahan ajar modul yang dikemas dengan prosedur pengemasan yaitu tahap perencanaan, tahap pelaksanaan dan tahap evaluasi. Modul yang disusun berisi Silabus, RPP dan materi pembelajaran tari Rapa’i Geleng berdasaran KD 3.1 yaitu konsep, teknik dan prosedur. Berdasaran uji kelayakan materi dan media didapat skor  4,66 dari uji validasi ahli materi, skor 4,6 dari uji validasi ahli media. Skor tersebut membuktikan bahwa modul pembelajaran tari Rapa’i Geleng ini sangat baik dijadikan bahan ajar oleh guru dalam pembelajaran tari pada siswa kelas XI Sekolah Menengah Atas.Kata Kunci: Pengemasan, Tari Rapa’i Geleng, Modul